Bibliometric analysis and visualisation of research on life cycle assessment in Africa (1992–2022) - Isah, Mohammed Engha; Zhang, Zhengyang; Matsubae, Kazuyo; Itsubo, Norihiro (The international journal of life cycle assessment, 2024)
Purpose Life cycle assessment (LCA) has found wide applicability as a tool for assessing the environmental impacts of human activities in different fields such as manufacturing, mining, transportation, oil and gas, construction, and medicine. Despite the wide applicability of LCA globally, the uptake and use of the tool in Africa remains limited. This research is motivated by the need to explore the continental structure of life cycle assessment to ascertain the level of knowledge and research; collaboration amongst institutions, countries, and authors; keyword co-occurrence; thematic evolution; and bibliographic coupling. Methods Publications related to life cycle assessment were retrieved and cleaned from the Scopus database with the language restricted to English and only countries recognised by the African Union. VOSviewer (version 1.6.19) visualisation tool was used to construct and visualise the network maps of researchers, co-occurrence, co-authorships, and keywords. On the other hand, Bibliometrix was employed to carryout descriptive analysis and thematic evolution and to extract bibliographic information. Results and discussion In total, 616 research publications between 1992 and 2022 were retrieved. The results show that research on the subject matter picked up from 2004 and has been on the upward trend. South Africa, Egypt, Tunisia, and Algeria are the top countries carrying out LCA research on the continent. In addition, the top authors, affiliations, and funders also come from these countries. It was also noted that there were low levels of cooperation between authors on the African continent; rather, they collaborate more with researchers in Europe, America, and other parts of the world. The built environment , construction industry , alternative energy , agriculture , and waste management and recycling are the major themes of research on the continent. Conclusion Life cycle assessment is gaining traction amongst researchers in Africa, albeit slowly. Considering the continents’ role in the future especially in providing critical raw materials needed for the transition to a carbon-neutral society in line with the Sustainable Development Goals (SDGs), rapid uptake and embedding life cycle thinking in every sector of the African economy are needed. However, there is an urgent need to equip researchers with the skills to facilitate the development of a life cycle inventory (LCI) database at countries or continental level.